Regulatory Barriers and the Principle of Non-discrimination in World Trade Law : Past, Present, and Future. - Cottier, Thomas; Mavroidis, Petros Constantinos; Blatter, Patrick (University of Michigan Press, 2010)
The University of Michigan Press is pleased to announce the second volume in an annual series, the World Trade Forum. The Forum's members include scholars, lawyers, and government and business practitioners working in the area of international trade, law, and policy. They meet annually to discuss integration issues in international economic relations, focusing on a new theme each year. The World Trade Forum 1998 deals with the issue of regulatory barriers. Contributors focus their attention on the implications that government intervention has on the principle of nondiscrimination, the cornerstone of the World Trade Organization. The chapters, which cover both the positive and the normative level, deal in particular with the issue of "like product" definition, and with mutual recognition agreements. The relevant WTO case law is presented and analyzed, and the roundtable discussions are primarily aimed at clarifying to what extent a constitutional function should be assigned to the WTO organs, if at all. Contributors include: Christoph Bail, Jacques Bourgeois, Marco Bronckers, Thomas Cottier, William Davey, Paul Demaret, Piet Eeckhout, Crawford Falconer, Olivier Guillod, Meinhard Hilf, Gary Horlick, Robert Howse, Robert Hudec, Patrick Low, Aaditya Mattoo, Petros C. Mavroidis, Patrick Messerlin, Damien Neven, Kalypso Nicolaidis, David Palmeter, Ernst Ulrich Petresmann, Andre Sapir, and Michel Waelbroeck. Thomas Cottier is Professor of Law, Institute of European and International Economic Law, University of Bern Law School. Petros C. Mavroidis is Professor of Law, University of Neuchâtel.